Cover crop productivity and subsequent soybean yield in the western Corn Belt. (4th May 2020) - Koehler‐Cole, Katja; Elmore, Roger W.; Blanco‐Canqui, Humberto; Francis, Charles A.; Shapiro, Charles A.; Proctor, Christopher A.; Ruis, Sabrina J.; Heeren, Derek M.; Irmak, Suat; Ferguson, Richard B.
Abstract: Cover crops (CC) in corn ( Zea mays L.) and soybean [ Glycine max (L.) Merr.] rotations may prevent N loss and provide other ecosystem services but CC productivity in the western Corn Belt is limited by the short growing season. Our objective was to assess CC treatment and planting practice effects on CC biomass, spring soil nitrate concentrations, and soybean yield at two rainfed sites in eastern and one irrigated site in south‐central Nebraska over 4 yr. Cover crop treatments (cereal rye [ Secale cereale L.] [RYE] and a mix of rye, legume, and brassica species [MIX]) were planted by broadcast interseeding into corn stands in September (pre‐harvest broadcast) or drilling after corn harvest (post‐harvest drilled) and terminated 2 wk before planting soybean. Cover crop biomass and N uptake varied between years, but generally at the eastern sites, pre‐harvest broadcasting produced more biomass than post‐harvest drilling (1.64 and 0.79 Mg ha −1, respectively) and had greater N uptake (37 and 24 kg ha −1, respectively). At the south‐central site, post‐harvest drilling produced more than pre‐harvest broadcasting (1.44 and 1.20 Mg ha −1, respectively). RYE had more biomass than MIX (1.41 and 1.09 Mg ha −1, respectively), but the same N uptake. Soil nitrate reductions after CC were small. In 3 of 12 site‐years, soybean yielded less after pre‐harvest CC. Yield reductions were not correlated to CC biomass, but were likely due to greater weed pressure. High CC productivity is necessary for high N uptake, and requires site‐specific selection of planting practice and CC treatments.